Response of Children with Stage IV Soft Tissue Sarcoma to Topotecan and Carboplatin: A Phase II Window Trial of the Cooperative Soft Tissue Sarcoma Group - Bochennek, K.; Dantonello, T.; Koscielniak, E.; Claviez, A.; Dirksen, U.; Sauerbrey, A.; Beilken, A.; Klingebiel, T. (Klinische Pädiatrie, 2013)
To investigate antitumor activity and toxicity associated with combined topotecan and carboplatin treatment in children and adolescents with metastasized, untreated soft tissue sarcoma (STS).Patients (n=34) less than 21 years old and untreated, stage IV STS. Patients were treated with topotecan (1 mg/m2/d for 4 days) and carboplatin (150 mg/m2/d for 4 days) (TC course) during week 1 and 4 of a chemotherapy window trial, which was followed by chemotherapy and local therapy from week 6 on. We evaluated the side effects, toxicity and tumor response (using RECIST criteria) 6 weeks after starting the 2 TC chemotherapy courses.The objective response rate (ORR) was 38% (n=13 patients with a partial response (PR)), and a stable disease (SD) was reached in 11 cases. No patient showed a complete response (CR) of all metastatic lesions, although 1 patient showed a CR of the target lesion. 2 patients died of progress of disease (PD). Toxicity was mainly hematological (grade III/IV toxicity 79%), and nonhematological toxicities mainly included infection, fever, nausea,and vomiting. Regarding adverse events, 4 probable and 8 possible events related to study medication occurred among the 66 courses of TC.In conclusion, TC was potent against high-risk STS, but results and toxicity data were not superior to former published monotherapeutic topotecan therapies.
Keywords: topotecan; carboplatin; metastasized sarcoma; soft tissue sarcoma; children; phase II window